CFD analyses on the thermal comfort conditions of a cooled room: a case study - Ozsagiroglu, Semih; Camci, Muhammet; Taner, Tolga; Acikgoz, Ozgen; Dalkilic, Ahmet Selim; Wongwises, Somchai (SPRINGER, 2022)
This study examined a room with a surface of 1.8 x 1.8 x 2.85 (m) and a well-insulated floor (adiabatic condition) and examined the heat exchange from the side surfaces and ceiling. In this closed room, the heat transfer effects with radiation were investigated while bringing them to comfort conditions ranging from 30 (degrees C) air temperature to 20-24 (degrees C). A computer with a power of 25 (W) as a source of heat, a person with an average metabolic activity of 50-70 (W) and a table were found in this closed room. In this study, the cooling of the room from the floor, ceiling and air conditioner was inquired while the computer was running, in a closed area under the specified heat transfer conditions. As a scenario, the air exchange coefficient was modeled via Ansys Fluent, fed with air of 15 (degrees C) with 1, 3, 5, 10, 15 air. In addition, the comfort values of the human wrist (the distance of 0.1 m) and the shoulder (the distance of 1.1 m) were researched according to ASHRAE-55. The obtained results were analyzed as a comparison of ACH results, and the comfort parameter values were analyzed by reading the sections taken from the ankle shoulder level and velocity, temperature, values according to ANSI/ASHRAE-55. The relative humidity was 50% in the room, while the metabolic activity is 1.2 (met). These parameters corresponded to the sitting position; the clothing effect was found to be 0.67 (clo). The novelty of this study encourages the production of the ideal CFD analysis on the thermal comfort conditions of a cooled room, the task of engineering.
Keywords: Comfort; Computational fluid dynamics; Floor cooling; Ceiling cooling; Air conditioner system; Ansys Fluent; PEM FUEL-CELL; ENERGY; TEMPERATURE; VELOCITY; Thermodynamics; Chemistry